The mediating role of the connection with nature in the relationship between behavioral problems and emotion regulation in early childhood - Aykut, Melike; Kara, H. Gözde Ertürk; Özyeter, Neslihan Tuğçe (Frontiers in Psychology, 2025)
IntroductionThis study aims to investigate the mediating role of connection to nature in the relationship between behavioral problems and emotion regulation in preschool children.MethodsA cross-sectional research design was used to collect data from a single time point. The study included 299 children (M < sub > age = 60.84 months, SD = 3.07). Children’s connection to nature was measured using the Disposition Toward Connecting with Nature Scale, emotion regulation skills were assessed with the Emotion Regulation Scale, and behavioral problems were evaluated using the Behavior Rating Scale.ResultsThe results indicated that there was a strong, statistically significant negative correlation between children’s connection to nature and behavioral problems (r = −0.884, p < 0.01), and a positive correlation with emotion regulation skills (r = 0.831, p < 0.01). Additionally, emotion regulation skills and behavioral problems demonstrated a strong, significant negative correlation (r = −0.772, p < 0.01). Bootstrap mediation analysis (PROCESS Macro Model 4) revealed that connection to nature partially mediated the relationship between behavioral problems and emotion regulation skills [indirect effect = −0.0231, BootSE = 0.0029, 95% CI (−0.0287, −0.0174)]. The direct effect of behavioral problems on emotion regulation remained significant (c’ = −0.028, p < 0.01), confirming partial mediation. This finding indicates that connection to nature is not the sole determining factor for children’s emotion regulation, but it plays a supportive role in enhancing their emotion regulation skills during this process. It has been observed that connection to nature can serve as a supportive factor for emotion regulation and may help children with behavioral issues cope more effectively with challenges in emotional management.DiscussionThese findings underscore the potential benefits of integrating nature-based activities into strategies that support children’s emotional development and may assist those with behavioral challenges.